2020
DOI: 10.1177/0956462420920145
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non-adherence to antiretroviral therapy among female sex workers living with HIV in Hyderabad, India

Abstract: We determined factors associated with non-adherence (consuming <90% of monthly antiretroviral therapy) among female sex workers (FSWs). An interviewer-administered questionnaire was used in a sample of 100 South Indian FSWs living with HIV. We examined demographics, food insecurity, side effects, stigma, alcohol/substance use and self-efficacy. Non-adherence was assessed by self-report, pill-count and combined measures. Prevalence ratios and 95% confidence intervals (CIs) were calculated at p-value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Although difficult to explain, the association between police violence and access to healthcare has been found at different levels [ 3 ]. Allam et al [ 35 ] showed that having been arrested in the last year was related to non-adherence to HIV treatment among FSW. Similarly, local pre-pandemic evidence showed an association between gender identity-related police discrimination and low adherence to HIV care among TW from Buenos Aires, Argentina; many of whom were engaged in sex work [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although difficult to explain, the association between police violence and access to healthcare has been found at different levels [ 3 ]. Allam et al [ 35 ] showed that having been arrested in the last year was related to non-adherence to HIV treatment among FSW. Similarly, local pre-pandemic evidence showed an association between gender identity-related police discrimination and low adherence to HIV care among TW from Buenos Aires, Argentina; many of whom were engaged in sex work [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of supportive environment, the vulnerability of personal privacy information to disclosure in the implementation of HIV health services, as well as AIDS-related discrimination and stigma pose a threat to the quality of health services, and have a serious impact on patients' mental health and the quality of health services. Research by Rames [39] and Yuchen Mao [40] suggests that social stigma is common, and this stigma and social stress can lead to depression, reduced quality of life and negative treatment outcomes. We suggested that regulatory agencies should work to reduce stigma effects.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the special nature of MSM population, the difference in public awareness, and the complexity of the public opinion environment, privacy disclosure in this population may cause physical and psychological harm and negative impact on personal life. Once their privacy is leaked, they may face problems such as discrimination, stigma, breakdown of social relationships, and even experience anxiety, depression, and other psychological disorders [38][39][40]. After receiving a reminder message, users may be likely to quickly close the page to prevent it from being seen by others.…”
Section: Principal Findingsmentioning
confidence: 99%